(untitled) (Semiárida, 2025)
Attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR) is a fast, sensitive, versatile, and non-destructive technique capable of an in situ evaluation of the adsorption of ions and molecules at the liquid-solid interface. This technique allows for studies in aqueous media, a task impossible with conventional FTIR due to interferences caused by water signals. The molecular information acquired by this technique allows the determination of the adsorption mode, including, in some cases, conformational and structural changes of the adsorbed substance. Furthermore, under properly controlled conditions, ATR-FTIR spectroscopy can be used as a quantitative tool to evaluate adsorption and desorption kinetics, and adsorption under equilibrium conditions. In this work, as an example, the ATR-FTIR spectroscopy is used to study the adsorption-desorption kinetics of different anions on goethite. The kinetics were monitored in situ with precise control of pH, temperature, and adsorbate concentration throughout the experiment using a flow cell. The results obtained are comparable with those obtained by the batch technique, with the advantage of being a faster technique, allowing information to be obtained in the first minutes of reaction and monitoring the identity of the surface species throughout the reaction time.